Pengaruh Model Pemecahan Masalah Polya Berbantuan LKPD Terhadap Kemampuan Menganalisis Materi Fisika Peserta Didik SMAN 1 Selong Tahun Pelajaran 2016/2017 - Masruhin Nur; Hairunnisyah Sahidu; Kosim Kosim (Department of Physics Education, Universitas Mataram, 2017)
This study aims to determine the effect of problem solving Polya model assisted by LKPD on the ability to analyze the physics of students. Type of this research is quasi experimental with research design untreated control group design with pre-test and post-test. The population is all students of class X. Samples are taken by using purposive sampling technique, so that the class X of MS 1 as experiment class and class X MS 2 as the control class. The analytical ability is measured by a written test in the form of a description. Based on the research result, the average value of the ability to analyze the experimental class students is 60,16 while the mean of the ability to analyze the control class is 41,53. The data capability of analyzing both classes is normally distributed and both homogeneous. Based on the test of hypothesis test-t polled variance, obtained tcount of 3.681. The ttable value for the data analysis ability of 1.996, at a significant level of 5%. The value of tcount is greater than ttable, meaning that there is influence of problem solving Ploya model with LKPD help on the ability of analyzing the physics of the students.